Imitating modelling of data processing in information system - Сафонов, Михайло Сергійович (Eastern-European Journal of Enterprise Technologies, 2014)
The information system with using distributed databases, where inquiry processing is performed in the order of the queue at each workstation is described. It is found that predictive methods are focused on the narrow use and not suitable for widespread use in information systems. The operation logic of the imitating model in terms of events, related to issuing commands from the main system to the control object is described. The steps to ensure that the data on the duration of executing the commands, received from control objects, turned into the probability density of random variables are defined. The relative frequency of events in the system is determined. Using predictive methods and knowledge about previous states of information system, progressive function, which can provide information about its future states with a certain probability, is formed. As well as all other imitating models with discrete events, this model describes the situation with the queue, in which data flows arrive from control objects before constructing the information system model. The considered system consists of one queue and N workstations (N control objects in information system). The queue is set by sequence of processing control objects in the initial priorities, calculated based on the workstation parameters. Empirical and theoretical functions of the system states are created. During the imitation, it was found that the average deviation of the theoretical distribution from empirical does not exceed 10% that indicates the feasibility of using the exponential function as predictive for the given system with the queue. Time of staying of the simulated system in the steady state is estimated and is equal to 2.7 seconds. It is concluded that this time is enough to predict the next state of information system that will allow timely and uniform load distribution among the workstations.